Special Aspects of Professional Activity of Motor Transport Profile Teaching Engineers - Hornostaieva, Olga; Kravchenko, Hanna (Educational Challenges, 2021)
The article characterizes the special features of the motor transport profile teaching engineers’ professional activity in vocational institutions (teacher of vocational training, master of vocational training), higher education institutions (engineering teacher) and in manufacturing. The purpose is to clarify the special aspects of motor transport profile teaching engineers’ professional training in higher education institutions of Ukraine. The following research methods are used observation, description through individual interviews, expert evaluation method and questionnaire. The results are the following. It is stated that engineering and pedagogical education involves the rational integration of psychological, pedagogical and engineering components of professional training. It is noted that the professional training of teaching engineers is aimed at the formation their professional engineering and professional pedagogical competencies. This integrated training includes two equivalent integrated components: engineering (technical and technological, manufacturing, special, industrial branch) and pedagogical (humanitarian and social). It is stated that successful professional activity of a teaching engineer of motor transport profile is connected with professional training in institutions of higher education and the content and organization of their self-education in the process of professional development. To ensure proper training of a teaching engineer for successful activities, it is necessary to keep a continuous connection between the engineering and technical awareness and pedagogical activities. Modern professional activity of a teaching engineer is characterized by their innovative activities, the specifics of them is caused by the peculiarities of professional-pedagogical education and conditions of engineering-pedagogical activities, which provide generation and transformation of new ideas into innovations and form the management system. The innovative activity of teaching engineer is the basis of creative approach to professional responsibilities. It is concluded that a teaching engineer of motor transport profile is a teacher with higher pedagogical and technical education, who performs educational-methodical, engineering-technical, scientific-innovative, communicative-psychological, organizational, managerial and legal activities.